Trends in Hyperglycemic Crisis Hospitalizations and in- and out-of-Hospital Mortality in the Last Decade Based on Korean National Health Insurance Claims Data - You, Ji Hong (Endocrinol Metab (Seoul), 2019)
BACKGROUND: Hyperglycemic crisis is a metabolic emergency associated with diabetes mellitus. However, accurate epidemiologic information on cases of hyperglycemic crisis in Korea remains scarce. We evaluated trends in hyperglycemic crisis hospitalizations and in- and out-of-hospital mortality in Korea. We also predicted future trends. METHODS: We extracted claims data with hyperglycemic crisis as the principal diagnosis from the National Health Insurance Service database in Korea from January 2004 to December 2013. We investigated the numbers of claims with hyperglycemic crisis and identified trends in hyperglycemic crisis based on those claims data. We predicted future trends by statistical estimation. RESULTS: The total annual number of claims of hyperglycemic crisis increased from 2,674 in 2004 to 5,540 in 2013. Statistical analysis revealed an increasing trend in hyperglycemic crisis hospitalizations (P for trend <0.01). In contrast, the hospitalization rate per 1,000 diabetes cases showed a decreasing trend (P for trend <0.01) during this period. The mortality rate per 1,000 diabetes cases also showed a decreasing trend (P for trend <0.0001). However, no distinct linear trend in the case-related fatality rate at <60 days over the last decade was observed. The predicted number of annual claims of hyperglycemic crisis will increase by 2030. CONCLUSION: The number of hyperglycemic crisis hospitalizations in Korea increased in the last decade, although the hospitalization rate per 1,000 diabetes cases and mortality rate decreased. Also, the predicted number of annual claims will increase in the future. Thus, it is necessary to establish long-term healthcare policies to prevent hyperglycemic crisis.